Are underground coal miners satisfied with their work boots?. (January 2018) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Steele, Julie R.
Abstract: Dissatisfaction with work boot design is common in the mining industry. Many underground coal miners believe their work boots contribute to the high incidence of lower limb injuries they experience. Despite this, the most recent research to examine underground coal mining work boot satisfaction was conducted over a decade ago. This present study aimed to address this gap in the literature by assessing current mining work boot satisfaction in relation to the work-related requirements for underground coal mining. 358 underground coal miners (355 men; mean age = 39.1 ± 10.7 years) completed a 54-question survey regarding their job details, work footwear habits, foot problems, lower limb and lower back pain history, and work footwear fit and comfort. Results revealed that underground coal miners were not satisfied with their current mining work boots. This was evident in the high incidence of reported foot problems (55.3%), lower back pain (44.5%), knee pain (21.5%), ankle pain (24.9%) and foot pain (42.3%). Over half of the underground coal miners surveyed believed their work boots contributed to their lower limb pain and reported their work boots were uncomfortable. Different working roles and environments resulted in differences in the incidence of foot problems, lower limb pain and comfort scores, confirming that one boot design cannot meet all the work-related requirements of underground coal mining. Further research examining the interaction of a variety of boot designs across the different underground surfaces and the different tasks miners perform is paramount to identify key boot design features that affect the way underground coal miners perform. Enhanced work boot design could improve worker comfort and productivity by reducing the high rates of reported foot problems and pain amongst underground coal miners. Highlights: Dissatisfaction with work boot design is common in the mining industry. Mining work boot satisfaction in relation to work-related requirements was assessed. Underground coal miners were not satisfied with their current mining work boots. There is still a high incidence of foot problems, lower back and lower limb pain. Foot problems, lower limb pain and comfort scores were task/environment specific.